Quantitative Trait Locus Mapping of Resistance to Turnip Yellows Virus in Brassica rapa and Brassica oleracea and Introgression of These Resistances by Resynthesis Into Allotetraploid Plants for Deployment in Brassica napus - Greer, Shannon F.; Hackenberg, Dieter; Gegas, Vasilis; Mitrousia, Georgia; Edwards, David; Batley, Jacqueline; Teakle, Graham R.; Barker, Guy C.; Walsh, John A. (Frontiers in Plant Science, 2021)
Turnip yellows virus (TuYV) is aphid transmitted and causes considerable yield losses in oilseed rape (OSR, Brassica napus, genome: AACC) and vegetable brassicas. Insecticide control of the aphid vector is limited due to insecticide resistance and banning of the most effective active ingredients in the EU. There is only one source of TuYV resistance in current commercial OSR varieties, which has been mapped to a single dominant quantitative trait locus (QTL) on chromosome A04. We report the identification, characterisation and mapping of TuYV resistance in the diploid progenitor species of OSR, Brassica rapa (genome: AA) and Brassica oleracea (genome: CC). Phenotyping of F1 populations, produced from within-species crosses between resistant and susceptible individuals, revealed the resistances were quantitative and partially dominant. QTL mapping of segregating backcross populations showed that the B. rapa resistance was controlled by at least two additive QTLs, one on chromosome A02 and the other on chromosome A06. Together they explained 40.3% of the phenotypic variation. In B. oleracea, a single QTL on chromosome C05, explained 22.1% of the phenotypic variation. The TuYV resistance QTLs detected in this study are different to that in the extant commercial resistant varieties. To exploit these resistances, an allotetraploid (genome: AACC) plant line was resynthesised from the interspecific cross between the TuYV-resistant B. rapa and B. oleracea lines. Flow cytometry confirmed that plantlets regenerated from the interspecific cross had both A and C genomes and were mixoploid. To stabilise ploidy, a fertile plantlet was self-pollinated to produce seed that had the desired resynthesised, allotetraploid genome AACC. Phenotyping of the resynthesised plants confirmed their resistance to TuYV. Genotyping with resistance-linked markers identified during the mapping in the progenitors, confirmed the presence of all TuYV resistance QTLs from B. rapa and B. oleracea. This is the first report of TuYV resistance mapped in the Brassica C genome and of an allotetraploid AACC line possessing dual resistance to TuYV originating from both of its progenitors. The introgression into OSR can now be accelerated utilising marker-assisted selection and this may reduce selection pressure for TuYV isolates able to overcome existing sources of resistance to TuYV.